A point-based semi-automatic expertise classification (PBaSE) method for knowledge management of an online special interest group - Ismail, Aisyah; Sulaiman, Salina; Sulaiman, Shahida; Sabudin, Maziani (2008)

(untitled)
An online Special Interest Group is a group of people with the same interest gather to form an online community through the Internet. In certain cases where the knowledge is being manipulated, the portal of a Special Interest Group is in a form of knowledge portal. This portal allows interaction among its community members. Interaction through forum in the portal makes activities such as discussion of problems and knowledge sharing among each other possible. The need to classify users’ expertise in a Special Interest Group is crucial task. This paper describes a Point-based Semiautomatic Expertise classification method to classify users’ expertise in a Special Interest Group knowledge portal